Performance Comparison Of Svpwm And Hysteresis Current Control For Dual Motor Drives - Mat Lazi, Jurifa; Ibrahim, Zulkifilie; Sulaiman , Marizan; Jamaludin, Irma Wani; Yusuf Lada, Musa (2011)
Dual motor drives fed by single inverter are purposely designed to reduced sizes and cost with respect to single motor drives fed by single inverter. This paper presents the speed responses behavior of Dual Permanent Magnet Synchronous Motor (PMSM) driven base on two different PWM control schemes, which are Space Vector Pulse Width Modulation (SVPWM) and Hysteresis Current Controller. These two techniques are compared for wide range of speed and for variation of load. MATLAB/Simulink has been chosen as the simulation tools. The comparison between SVPWM controller and Hysteresis Current Controller for Dual PMSM fed by single inverter is presented. Both techniques show satisfactory speed regulation for a wide range of speed either with load, no load or variation of load.